2013
DOI: 10.1590/s1516-635x2013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fiber and genetic strain on the performance and energy balance of broiler chickens

Abstract: The experiment was conducted to evaluate the effect of dietary fiber on the performance and energy balance of broiler chickens of a fast-growing strain (Cobb500) and a slow-growing strain (Label Rokens during the period of 1 one to 42 days of used In total, 360 male broilers (240 fast-grorain and 120 slow-grtrain)were, housed in collective cages. A completely randomized experimental dewith in a 3x2 factorial arrangement was applied, consisting of three groups of birds (slow-growing-SG; fast-growing fed ad libi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 10 publications
1
17
1
3
Order By: Relevance
“…In contrast with our study, some authors found that the use of yeast cell in broiler diets improved feed conversion ratio [17]. This may be because that in the previous study high-fiber (5.02%) and low-protein (18%) diets were used, and it has been reported that high-fiber diet [23] and low-protein diet [24] reduce feed efficiency. The results of the effects of dietary yeast supplementation on carcass weight and relative organs weight are presented in Table 4.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast with our study, some authors found that the use of yeast cell in broiler diets improved feed conversion ratio [17]. This may be because that in the previous study high-fiber (5.02%) and low-protein (18%) diets were used, and it has been reported that high-fiber diet [23] and low-protein diet [24] reduce feed efficiency. The results of the effects of dietary yeast supplementation on carcass weight and relative organs weight are presented in Table 4.…”
Section: Resultscontrasting
confidence: 99%
“…Conventionally, insoluble non‐fermentable dietary fibre (DF), including cellulose and lignin, is considered as a diluent of a diet, which can affect energy balance of broiler chickens, reducing the digestibility of nutrients and the metabolisable energy level in poultry feeds (Jørgensen et al., ; Cao et al., ; Krás et al., ). However, recent research performed on broilers have shown that limited amounts of insoluble DF in the chicken diet prevent intestinal dysfunction by stimulating gastrointestinal tract development, growth of beneficial gut bacteria, activity of pancreatic enzymes, and bile acid secretion and thus improve digestive function (Hetland and Svihus, ; Cao et al., ; Hetland et al., ; González‐Alvarado et al., ; Jiménez‐Moreno et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, the basal diet was 30% substituted with test ingredients so the replacement of ingredients with higher fiber content resulted in increased dietary fiber. Kras et al (2013) documented poor performance and lower energy retention in birds fed high fibrous diet. The lowest (P<0.05) ADFI of RB's diets might be due to its more AMEn content.…”
Section: Discussionmentioning
confidence: 98%